Respuestas
Respuesta dada por:
1
Javier=5cesar
si a César llamamos "x" entonces Javier es '5x'
ahora dentro de 6 años
Javier tendrá "5x+6" y César tendrá "x+6"
ahora planteas la actuación
5x+6=3(x+6)
5x-3x=18-6
2x=12
x=6
César =x=6
si a César llamamos "x" entonces Javier es '5x'
ahora dentro de 6 años
Javier tendrá "5x+6" y César tendrá "x+6"
ahora planteas la actuación
5x+6=3(x+6)
5x-3x=18-6
2x=12
x=6
César =x=6
hdxbudx:
muchisimas gracias
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años